EMISSION OF THE MIXTURES OF INERT GASES WITH HALOGENIDES AT IONISED PUMPING - Khasenov, M. U. (Recent Contributions to Physics, 2009)
Spectra of a luminescence of mixes of inert gases with NF3 and CCl4 are investigated at excitation by α-particles of 210Po. Spectra will consist of several bands, the most intensive band is identified with B - X transition. For Ar (1.5 atm) + Xe (40 Torr) + CCl4 (0.7 Torr) mixture the factor of transformation of a nuclear energy into emission in a band of 308 nm is appreciated: η ~11 %.
Keywords: light